Investigations in neural network learning using geometrical approach - Wang, Di (2008)
In this thesis several methods to control the geometrical expansion process are proposed and analyzed. Our approaches turn out to gain faster training speed with satisfactory accuracy. We discuss problems both with Boolean inputs and with real-valued inputs respectively.